Kualitas Mikroskopis Semen Ayam Kampung yang Disumplementasikan L-Arginine dan L-Lysine HCl Dalam Pakan - Yuliana Mau; Agustinus Agung Dethan; Charles V. Lisnahan (JAS, 2022)
This study aims to determine the quality of semen microscopically in male free-range chickens supplemented with L-Arginine and L-Lysine in the feed. The study used 43 male free-range chickens aged 3 months, and data collection was taken when the chickens were 5 months old. The treatments consisted of T1: control feed + L-Arginine 0,4 g + L-Lysine 0,6 g; T2: Control feed + L-Arginine 0,6 g + L-Lysine 0,6 g; T3: Control feed + L-Arginine 0,4 g + L-Lysine 0,8 g; and T4: Control feed + L-Arginine 0,6 g + L-Lysine 0,8 g. The variables observed in this study were motility, viability, and spermatozoa abnormalities. The highest mean mass motility value was found in treatment (T4) of 2,6±0,93 and individual motility, the highest average value was also found in (T4) 80±13,32%, the highest mean viability was found in (T2) of 95±1,58%, and the lowest mean abnormal is found in (T1) of 13,5±1,60%. Statistical analysis showed that the administration of the amino acids L-Arginine and L-Lysine with different levels had a significant effect on viability while on mass motility; individual motility and abnormal spermatozoa had no significant effect. It was concluded that the use of L-arginine 0,6 g and L-lysine 0,6 g supplemented in the free-range chicken feed had a significant effect on spermatozoa viability while mass motility, individual motility and abnormal spermatozoa had no significant effect.